Biogeografi Flindersia pimentelliana F. v. Muell. PADA KAWASAN HUTAN BEMBAB KABUPATEN MANOKWARI SELATAN - Rusdi Angrianto; Zainal Zainal; Rima H S Siburian (Jurnal Hutan Tropis, 2019)
Forests in Papua have a high diversity of tree species, with diverse topography. Biogeography is thought to have an impact on the presence of a species. Therefore, research on biogeography of Flindersia pimelentianna F. v. Muel will be an important information in the development of this type. The method used in this study is biogeographic factor survey and analysis. The results indicated that the physiographic factors that influence the location for the plant growth is the slope level, the altitude, as well as temperature, inertia and topography. Whereas the growing site of this plant is commonly found in calcareous and alluvial soils with karts and rocky conditions. This type is generally associated with Euphorbiaceae with the demographic aspect in  B strata.